Hořava gravity after GW170817 - Emir Gümrükçüoğlu, A.; Saravani, Mehdi; Sotiriou, Thomas P. (American Physical Society, 2018)
The recent detection of gravitational wave GW170817 has placed a severe bound on the deviation of the speed of gravitational waves from the speed of light. We explore the consequences of this detection for Hořava gravity.